Optimal adaptive Jacobian internal forces controller for multiple whole-limb manipulators in the presence of kinematic uncertainties. (August 2018) - Abdeetedal, Mahyar; Rezaee, Hamed; Talebi, Heidar A.; Abdollahi, Farzaneh
Highlights: We study control of multiple whole-limb manipulators with kinematic uncertainties. Power grasping in the presence uncontrollable contact forces is considered. An algorithm for optimizing the contact forces is introduced. An adaptive Jacobian controller for internal force regulation is proposed. Experimental results demonstrate the validity of the proposed strategy. Abstract: The power grasping problem in robot manipulators in the presence of kinematic uncertainties and uncontrollable forces is studied in this paper. We consider a whole-limb manipulator system able to use not only its end-effector but also all other parts of its body for manipulation and grasping. Accordingly, grasping is not limited to wrapping the robotic arm around the object, and the desired force can be applied in contact points. By proposing an optimal adaptive control scheme, optimal contact forces are shown to be regulated by force decomposition. Power grasping in the presence of kinematic uncertainties and uncontrollable contact forces for multiple whole-limb manipulators is the main contribution of the paper as compared to existing results in the literature. Experimental results demonstrate the validity of the proposed control strategy.